Bir Petrol Tankeri Buhar Güç Sisteminin Ekserji Analizi - Çiçek, Abdurrahman Nuri (Fen Bilimleri Enstitüsü, 2009)
Bu çalışmada, 17 MW gücünde buhar tesisine sahip bir ham petrol tankeri incelenmiştir. Bu gemide buhar, hem türbinlerde genişletilerek gemi güç üretimi ve tahriki için hem de kargo tanklarının ısıtılması ve gemide buhardan yararlanan diğer servisler için kullanılmıştır. Gemi makine dairesinin içindeki tam yükte güç üreten buhar türbinli bu sistem için ekserji analizi yapılarak sistemde meydana gelen tersinmezlikler hesaplanmıştır. Bu çalışmada hesaplamalar için Cycle-Tempo adındaki Delft Teknik Üniversitesi tarafından hazırlanan bir termodinamik analiz programı kullanılmıştır. Çalışmada programın işlevselliğini örneklemek için basit bir Rankine çevrimi modellenip ve sonuçları gösterilecektir. Daha sonra üstünde uğraşılan buhar tesisinin modelini oluşturup enerji ve ekserji analizi yapılacaktır. Sonuçları değerlendirilip hem sistem genelinde hem de her bir komponent için tersinmezlik incelenecektir. Çevrimdeki yoğuşturucunun ısıl denge modeli çıkarılacak ve soğutma suyu sıcaklığının performans üzerine olan etkileri incelenecektir. Geminin farklı çevre sıcaklıklarında ve farklı yüklerde çalışma şartlarında performansı gözden geçirilmiştir.

In this study, a crude oil tanker which has 17 MW power steam plant has been examined. The steam in this ship both was used for power production and propulsion of the vessel and meanwhile, by taking advantage of steam, for heating of cargo tanks and other ancillary services in the ship as well. The irreversibility occurred in the system has been calculated by carrying out on exergy analysis for this system having steam turbine, working at full load in the vessel’s engine room. For computations in this study a thermodynamic analysis program named the Cycle-Tempo which has been developed by the Delft Technical University was employed. In order to exemplify the functionality of the program in our study, a simple Rankine cycle was modeled and its results have been demonstrated. Afterwards, an exergy analysis is performed by setting a conceptual model of the steam plant and thereafter assessing the conclusions thereof, while scrutinizing irreversibility both throughout the system and for each component. The influence of the cooling water temperature on the thermal efficiency of a conceptual model is studied through an energy and exergy analysis based on the first and second law of thermodynamics to gain some new insights into the plant performance. The effects of the load variations and ambient temperature are calculated in order to obtain a good insight into this analysis.
Exergy Analysis Of A Crude Oil Carrier Steam Plant
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2009
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2009
Keywords: enerji; ekserji; ekserji analizi; gemi güç üretimi; buhar türbini; petrol tankeri; buhar tesisi; energy; exergy; exergy analysis; ship power generation; steam turbine; crude oil carrier; steam plant